Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 3(x-2)(x+2) < 3x2 + x
3(x2 + 2x - 2x - 4 ) < 3x2 + x
<=> 3x2 + 6x - 6x - 12 < 3x2 + x
<=> 3x2 + 6x - 6x - 3x2 - x < 12
<=> x > -12
Vậy bpt có nghiệm là x > -12.
b) ( x+4 )(5x-1) > 5x2 + 16x + 2
<=> 5x2 - x + 20x - 4 - 5x2 - 16x - 2 > 0
<=> 5x2 - x + 20x - 5x2 - 16x > 2 + 4
<=> 3x > 6
<=> x > 2
Vậy btp có nghiệm là x > 2
Giải:
a) \(3\left(x-2\right)\left(x+2\right)< 3x^2+x\)
\(\Leftrightarrow3\left(x^2-4\right)< 3x^2+x\)
\(\Leftrightarrow3x^2-12< 3x^2+x\)
\(\Leftrightarrow-12< x\)
\(\Leftrightarrow x>-12\)
Vậy ...
b) \(\left(x+4\right)\left(5x-1\right)>5x^2+16x+2\)
\(\Leftrightarrow5x^2+20x-x-4>5x^2+16x+2\)
\(\Leftrightarrow5x^2+19x-4>5x^2+16x+2\)
\(\Leftrightarrow3x-4>2\)
\(\Leftrightarrow3x>6\)
\(\Leftrightarrow x>2\)
Vậy ...
b, \(\frac{5x+1}{x+3}-\frac{3x-2}{x-1}=\frac{5.\left(x+3\right)-14}{x+3}-\frac{3\left(x-1\right)+1}{x-1}=5-\frac{14}{x+3}-3+\frac{1}{x-1}=2+\left(\frac{1}{x-1}-\frac{14}{x+3}\right)=2+\left(\frac{x+3-14x+14}{x^2-x+3x-3}\right)=2+\left(\frac{17-13x}{x^2+2x-3}\right)>2\)